Role of minimally invasive glaucoma procedures increasing the outflow of aqueous humor through the conventional pathway in advanced treatment of glaucoma - Kempys, Łukasz; Mrukwa-Kominek, Ewa (Klinika Oczna / Acta Ophthalmologica Polonica, 2024)
The objective of glaucoma surgery is to prevent the progression of the disease. In practice, surgical treatment of glaucoma is typically undertaken when pharmacotherapy is ineffective, poorly tolerated, contraindicated, or improperly used by the patient. Minimally invasive glaucoma surgery (MIGS) represents one of the latest advancements in surgical approaches for managing glaucoma. MIGS is mainly used in the treatment of primary open-angle glaucoma and some types of secondary open-angle glaucoma, in particular pseudoexfoliation glaucoma. Minimally invasive glaucoma procedures to increase the outflow of aqueous humor via the conventional route, including ab interno goniotomy with the Kahook blade, iStent, Hydrus Microstent, Trabectome, excimer laser trabeculotomy, ab interno canaloplasty, and gonioscopy-assisted transluminal trabeculotomy are considered to be the safest. Another benefit of MIGS is the possibility to perform the surgical procedure concurrently with cataract phacoemulsification, while also preserving the bulbar conjunctiva, thereby enabling potential future procedures, if needed. An analysis of the outcomes of studies on standalone MIGS procedures improving aqueous humor outflow via the conventional pathway, as well as combined procedures with cataract phacoemulsification, shows their high efficacy in lowering intraocular pressure and reducing the number of active substances used for treatment, which crucially contributes to the success of glaucoma therapy, preservation of functional visual acuity, and improvement in the quality of life for patients. The aim of this study was to review the literature on the topic of minimally invasive glaucoma procedures increasing the outflow of aqueous humor via the conventional pathway.